Modal Analysis of a Certain Light Truck Powertrain Structure - Zhang Zhengpeng; Ma Weijin; Yang Bo; Wang Junyuan; Zhang Jiping; Ge Yumin (Jixie chuandong)
Due to the complexity of light truck powertrain vibration shape,the structure weak parts is easy to motivate and cause resonance phenomenon.In order to obtain the powertrain dynamic characteristics,by using the finite element method and PolyMAX method,simulation and experiment modal analysis for light truck powertrain are respectively carried out.By analyzing and comparing the results of both,the dynamic characteristic of the light truck powertrain is effectively reflected,the reliability and rationality are proved.The theory basis for the fault diagnosis and dynamic optimization design of the light truck powertrain are provided.